Pandangan Bioetik pada Penghentian Terapi Penunjang Hidup dalam Perawatan Paliatif - Agrevina Ane Lukito; Gabriel Tandecxi; Celine Aprillia Hartawan; Clarissa Frances Mandita Putri; Elisabeth Eileen Santoso; Farrel Zefanya R. Hartoyo; Nathalie Cynthia; Novia; Stephanie Aurelia Wirawan; Valentino; Liauw Djai Yen (Universitas Udayana, 2025)
The advancements in modern medicine and current medical technology have extended life expectancy and altered the natural norms of death. However, dilemmas can arise in cases where patients show no positive response or significant improvement in their condition, thus rendering treatment deemed futile. One solution is to discontinue life-sustaining therapy, a decision made by the physician or with the consent of the patients and their families. Such circumstances can increase moral, ethical, and legal burdens. Hence, this research is conducted to reaffirm the rights of patients and their families and provide more detailed legal guidance to responsible physicians. This is a literature review. References used are literature from journal articles published at national and international levels, spanning publications in English and Indonesian. In clinical practice, considerations in decision-making or discontinuation of life-sustaining therapy must be accompanied by multidisciplinary collaboration among several doctors, patients, and patient families. The ethics involved in discontinuing life sustaining therapy are highly complex, thus requiring extensive deliberation in assessing medical rationale accurately and the applicable laws in a region or country. Effectively navigating the complexities surrounding the initiation or cessation of life sustaining interventions requires multidisciplinary collaboration involving healthcare professionals, patients, and their families. Furthermore, a profound understanding of medical and ethical aspects is essential to mitigate potential conflicts and legal ramifications.